OVERPRESSURE DISTRIBUTION AND ITS GENERATING MECHANISM IN THE ONSHORE NORTHERN PORTION OF EAST JAVA, EAST JAVA BASIN - HAKIM, FAHMI
The northern portion of East Java is a part of The East Java Basin. This area is chosen as the research area because it has indications of the presence of overpressure and possessing complex geological conditions such as: variation in basement depth and the occurrence of several sedimentation zones. Such geological conditions will affect the distribution and generating mechanism of overpressure.